The high-velocity clouds and the Magellanic Clouds - Olano, Carlos Alberto (2004)
The majority of the high-velocity clouds (HVC) having a common origin linked to the dynamic evolution of the Magellanic Clouds was discussed. It was concluded that the HVC surround the Galaxy, forming a metacloud of ∼300 kpc in size and with a mass of ∼3×109 M⊙. It was found that the HVC were the product of a powerful superwind, which occurred in the Magellanic Clouds about 570 Myr ago as a consequence of the interaction of the Large and Small Magellanic Clouds. The effects of the passage of the HVC flow through the Galactic disk produced on the interstellar medium were also analyzed.